Primary extragastrointestinal stromal tumor of greater omentum misdiagnosed as an adnexal tumor: a case report - Jaafar, Wissal; Medemagh, Malek; Godcha, Samar; Chiba, Yasmine; B. Fekih, Ichrak; Mhiri, Karima; Khalifa, Nahed; Mourali, Mechaal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Gastrointestinal stromal tumors (GISTs) are the most frequently occurring mesenchymal tumors in the gastrointestinal system. These tumors are believed to arise from interstitial cells of Cajal, the gastrointestinal pacemaker cells, due to the presence of tyrosine kinase receptors in their tissue. When tumors with similar morphological and immunohistochemical properties are found outside the gastrointestinal tract such as the mesentery, retroperitoneum, and every now and then the omentum, they are classified as extragastrointestinal stromal tumors (EGISTs). We report a case of a primary epithelioid (EGIST) of the greater omentum, the tumor was diagnosed in women with non-specific symptoms who presented for abdominal pain initially misdiagnosed as an adnexal tumor. This report highlights the need to consider EGIST in the differential diagnosis of abdominal and pelvic tumors and underscores the importance of EGIST-specific studies to evaluate treatment modalities for improved oncological outcomes and quality of life.